2019
DOI: 10.33265/polar.v38.3605
|View full text |Cite
|
Sign up to set email alerts
|

Diving behaviour of adult male white whales (Delphinapterus leucas) in Svalbard, Norway

Abstract: Bt: bottom time (duration in seconds) Dmax: maximum depth recorded for a given dive (in metres) Dt: dive time (duration in seconds) residual Bt_DDt: residual of the relationship between the bottom duration and both the maximum depth and the dive duration SD: standard deviation SE: standard error SRDL: satellite-relay data logger St: surface time (duration in seconds), i.e., time spent at the surface between dives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Dives represented by the Shallow V type are often regarded as transiting or recovery type dives (Lefebvre et al, 2018;Vacquié-Garcia et al, 2019), which is supported here by the slow rates of vertical movement, shallow depths, and the high frequency of occurrence of this dive type throughout the year (Figure 8). Furthermore, EBS belugas spent less time at the surface after Deep Benthic or Deep Pelagic V dives when followed by a Shallow V dive (Supplementary Table 3b), which could represent recovery, or digestion of prey after foraging.…”
Section: Transiting and Recovery Divesmentioning
confidence: 58%
See 1 more Smart Citation
“…Dives represented by the Shallow V type are often regarded as transiting or recovery type dives (Lefebvre et al, 2018;Vacquié-Garcia et al, 2019), which is supported here by the slow rates of vertical movement, shallow depths, and the high frequency of occurrence of this dive type throughout the year (Figure 8). Furthermore, EBS belugas spent less time at the surface after Deep Benthic or Deep Pelagic V dives when followed by a Shallow V dive (Supplementary Table 3b), which could represent recovery, or digestion of prey after foraging.…”
Section: Transiting and Recovery Divesmentioning
confidence: 58%
“…For example, summarized histogram data that reduce battery drain have often been used to examine depth use in belugas (e.g., Heide-Jørgensen et al, 1998;Goetz et al, 2012;Hauser et al, 2015; note some older tags were only capable of collecting these data), but this type of data can limit inferences on behavior. While a few studies on belugas have analyzed data on individual dives, these typically cover short time periods, primarily the summer and fall (e.g., Martin and Smith, 1992;Richard et al, 1997;Lefebvre et al, 2018;Vacquié-Garcia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hauser et al (2015) reported that belugas on the shelf of the Beaufort Sea often dove to the bottom, which was not greater than 100 m depth, and dives of less than 10 m are common among belugas in the shallow Bristol Bay and Cook Inlet, Alaska (Goetz et al 2012;Laidre et al 2017). Male belugas off Svalbard dive to less than 5 m approximately 60% of the time, even in deep water (Vacquie-Garcia et al 2019). However, six belugas tagged near Devon Island, Canada, spent only 20-39% of their time at a depth less than 5 m and had a maximum dive depth of 872 m (Heide-Jørgensen et al 1998).…”
Section: Beluga Dive Behaviourmentioning
confidence: 99%
“…The longest reported dive duration for a beluga is 31.4 min (Vacquie-Garcia et al 2019); average dive durations range from 1.1 to 18 min (Ridgway et al 1984;Martin et al 1998;Martin & Smith 1999;Kingsle et al 2001;Martin et al 2001;Goetz et al 2012;Citta et al 2013;Vacquie-Garcia et al 2019). Deeper dives are usually longer in duration (Martin & Smith 1999;Citta et al 2013) but may have shorter bottom times or time spent foraging (Martin & Smith 1999).…”
Section: Beluga Dive Behaviourmentioning
confidence: 99%
“…Morphological features of belugas such as epidermal proliferation and moulting also cycle annually, seemingly correlated with migration (St. Aubin et al 1990;Smith et al 1992). Further, the movements of belugas reflect the season (Vacquié-Garcia et al 2019), with belugas often inhabiting more shallow, brackish water in the summer months and open waters in the winter months (Doan & Douglas 1953;Sergeant 1973;Lydersen et al 2001). Similarly, in the case of the Cook Inlet beluga population, high-density congregations are associated with foraging opportunities that peak in June and early July (Castellote et al 2020), and the proportion of adults and juveniles within a group vary depending on the calendar month (McGuire et al 2020).…”
Section: Introductionmentioning
confidence: 99%